Triathlon: Ergo Nutrition for Training, Competing, and Recovering - Miguel-Ortega, Álvaro; Rodríguez-Rodrigo, María-Azucena; Mielgo-Ayuso, Juan; Calleja-González, Julio (Nutrients, 2025)
Triathlon is a multi-sport event that combines swimming, cycling and running. The distances vary and the physiological demands are high. Objectives: This review compiles information on nutritional strategies and ergogenic supplements for triathlon training, competition and recovery. It aims to provide an understanding of the specific challenges and needs of the sport to help triathletes and coaches optimise performance through effective training and nutrition plans. Methods: English-language publications were searched using the keywords triathlon, nutrition, recovery and ergogenic aids, alone or in combination, in databases. Results: Maintaining good glycogen levels, consuming enough carbohydrates and staying properly hydrated are key to athletic performance, especially for triathletes. Education regarding nutrition, the role of probiotics and supplements, and diet modification for the enhancement of performance and recovery are pivotal considerations. Conclusions: Triathletes are at risk of RED-S due to negative energy balance and high fibre/plant protein diets, especially women. Optimising muscle glycogen through tailored diet and training, especially pre- and in-race nutrition, including carbohydrate loading and hydration strategies, is critical. Education is needed to improve post-exercise nutrition, while probiotics and certain supplements may aid performance and recovery. Dietary support is important for resistance training to optimise performance and recovery.